Das Kaufmännische: Kaufmännische Bildung in der Ausbildungsvorbereitung - Kremer, H.-Hugo; Kallenbach, G.; Sprey, M. (Kaufmännische Bildung. Sondierungen zu einer vernachlässigten Sinndimension)

Implementing Outcome-Oriented Study Programmes at University: The Challenge of Academic Culture - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
In recent years, the design of study programmes in Higher Education (HE) has been given considerable attention by HE practitioners and researchers. Today, a sound body of concepts and experiences on different realisations of Bologna-conforming study programmes is available. The same, however, does not hold true for questions concerning the processes of implementing and further developing programmes. This paper investigates the challenges related with implementation, particularly at universities. A first aim is to understand the specifics of academic culture and their significance for programme implementation and development. Elaborating on this analysis, a second aim is to outline the role of educational developers in this process, as well as the necessary competencies to perform such a role.
Keywords: Programmentwicklung; Studienprogramme; program development; educational development; academic culture; disciplinary culture

Constitutions and Social Networks - Mauleon, Ana; Röhl, Nils; Vannetelbosch, Vincent
The objective of this paper is to analyze the formation of group structures where individuals are allowed to engage in several groups at the same time. These structures are interpreted here as social networks. Each of the groups is supposed to have specific rules or constitutions governing which members may join or leave it. A social network is then considered to be stable if none of the groups is altered any more. Given this framework, we not only analyze which influence the constitutions have on network formation but we also provide requirements under which stable networks are induced for sure. Furthermore, by embedding many-to-many matchings into our setting, we apply our model to job markets with labor unions. To some extent the unions may provide job guarantees and, therefore, have influence on the stability of the job market.

Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change - Mir Djawadi, Behnud; Fahr, Rene; Turk, Florian (Value in Health)
BackgroundMedical nonpersistence is a worldwide problem of striking magnitude. Although many fields of studies including epidemiology, sociology, and psychology try to identify determinants for medical nonpersistence, comprehensive research to explain medical nonpersistence from an economics perspective is rather scarce.ObjectivesThe aim of the study was to develop a conceptual framework that augments standard economic choice theory with psychological concepts of behavioral economics to understand how patients’ preferences for discontinuing with therapy arise over the course of the medical treatment. The availability of such a framework allows the targeted design of mechanisms for intervention strategies.MethodsOur conceptual framework models the patient as an active economic agent who evaluates the benefits and costs for continuing with therapy. We argue that a combination of loss aversion and mental accounting operations explains why patients discontinue with therapy at a specific point in time. We designed a randomized laboratory economic experiment with a student subject pool to investigate the behavioral predictions.ResultsSubjects continue with therapy as long as experienced utility losses have to be compensated. As soon as previous losses are evened out, subjects perceive the marginal benefit of persistence lower than in the beginning of the treatment. Consequently, subjects start to discontinue with therapy.ConclusionsOur results highlight that concepts of behavioral economics capture the dynamic structure of medical nonpersistence better than does standard economic choice theory. We recommend that behavioral economics should be a mandatory part of the development of possible intervention strategies aimed at improving patients’ compliance and persistence behavior.

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)
We consider the inner core as a solution concept for cooperative games with non-transferable utility (NTU) and its relationship to payoffs of competitive equilibria of markets that are induced by NTU games. An NTU game is an NTU market game if there exists a market such that the set of utility allocations a coalition can achieve in the market coincides with the set of utility allocations the coalition can achieve in the game. In this paper, we introduce a new construction of a market based on a closed subset of the inner core which satisfies a strict positive separability. We show that the constructed market represents the NTU game and, further, has the given closed set as the set of payoff vectors of competitive equilibria. It turns out that this market is not uniquely determined, and thus, we obtain a class of markets. Our results generalize those relating to competitive outcomes of NTU market games in the literature.

Developing study programs as a continuous task-the role of educational developers - Brahm, Taiga; Zellweger, Franziska; Jenert, Tobias; Thomann, Geri
Abstract Summary: Study programs are currently receiving more attention in Europe. In consequence, it can be observed that the roles of program development and management are professionalized. In the proposed round table, we would like to discuss the role of educational developers to support this professionalization via measures of training and process support in the light of recent developments in Switzerland. Abstract Text: Professionalization of program development as an institutional responsibility In Switzerland, different developments in higher education have led to increased attention to the development and management of the study programs such as the Bologna process, an increasingly competitive environment, the tertiarisation of a number of professions formerly acquired through vocational education. Furthermore, the national qualification framework and in particular accreditation processes require HEI to demonstrate the effectiveness of their activities (e.g., Sursock & Smit, 2010). Many different actors have been involved in development processes on the program level but also within educational development units. However, so far a systematic discourse on key issues regarding the management and development of study programs is missing, not only in German-speaking Europe. The following main question will guide the round table session: How can educational development give vital impulses for program development? Our starting points are two approaches or frameworks from Swiss HEI: a) the definition of competencies for new program professionals at the Zurich University for Teacher Education and b) a process for the strategic development of didactically-aligned study programs at the University of St. Gallen. Framework 1: Competencies for program managers The experiences with a training program for study program managers at the Zurich University for Teacher Education are reported. Over a period of four years, a competency profile has been developed and refined. Insights into the challenges and struggles of this role were gained. Despite diverse job characteristics of program managers (often resulting from an institution-specific history), there is a common set of competencies necessary to successfully cope with organizational complexity such as role competency (Schein, 1992) and lateral leadership (Kühl et al., 2005). Framework 2: Towards a systematic development of study programs The second initiative concerns the strategic approach to program development implemented at the University of St. Gallen (Brahm & Jenert, 2013; Jenert, 2011). In this structured process, the program goes through four process steps: process initiation, program analysis, program development, evaluation of the process and results. A major challenge in this process is the role of program professionals. The goal is to establish them as change agents for a didactically-aligned study program. Outcome: Role of educational development After briefly introducing the two examples, the roles of program professionals and educational development in HEI will be discussed. The questions guiding the discussion will be: • How can program development be established as a continuing task, closely tied to quality development? • How can the competencies of program professionals be developed and the local capacity and ownership be strengthened? • How can educational development support program development and provide vital impulses? Audience Engagement. Depending on the number of participants, first the questions will be discussed in groups. To put the results of the discussion on record, it will be summarized and uploaded in our weblog for further discussion after the session.
Keywords: curriculum development; study programs; Bologna; educational development; higher education

Entwicklung der Motivation von Studierenden der Wirtschafts-wissenschaften im ersten Studienjahr-eine Mixed-Methods-Studie - Jenert, Tobias; Brahm, Taiga
Das erste Studienjahr wird als wesentlicher Übergang von der Schule in die Hochschule angesehen. Im Vordergrund steht dabei häufig die Fragen der Identitätsfindung der Studierenden und das "Ankommen" im neuen Lebensabschnitt (Briggs, Clark, & Hall, 2012; Scanlon, Rowling, & Weber, 2007). In diesem Zusammenhang werden ganz unterschiedliche Aspekte untersucht, z. B. die vorhandenen Lernkompetenzen oder das Zeitmanagement der Studierenden (Barron & D'Annunzio-Green, 2009), vorhandene Einführungsprogramme an Hochschulen (z.B. Gale & Parker, 2012) oder dem ‚student engagement‘ während des ersten Jahres (Krause & Coates, 2008). Obwohl die Motivation der Studierenden als starker Prädiktor für die Leistung angesehen wird (z. B. Busato, Prins, Elshouta, & Hamaker, 2000), wurde die Motivationsentwicklung im ersten Studienjahr bis dato nur selten betrachtet. Die vorliegende Mixed Methods-Studie setzt an dieser Forschungslücke an und untersucht die Entwicklung der Studienmotivation von Wirtschaftsstudierenden im Verlauf des ersten Studienjahres. Im Rahmen einer quantitativen Längsschnittuntersuchung mit drei Messzeitpunkten wird dabei die Motivationsentwicklung über die gesamte Studierendenpopulation hinweg erfasst. Im Mittelpunkt steht die Frage, wie sich die intrinsische und extrinsische Studienmotivation sowie die studienbezogene Selbstwirksamkeit über das erste Studienjahr verändern. Zudem wird untersucht, inwiefern verschiedene studienbezogene Variablen (z. B. Angst) sich auf die Motivationsentwicklung auswirken. Um vertiefte Erkenntnisse über die Bedeutsamkeit verschiedener Gestaltungsmerkmale des ersten Studienjahres auf die Motivationsentwicklung der Studierenden zu gewinnen, wurde parallel zur quantitativen Untersuchung eine qualitative Längsschnittstudie durchgeführt mit dem Ziel, (1) verschiedene Verläufe der Motivationsentwicklung und (2) kritische Ereignisse im Eingangsjahr zu identifizieren. Das vorliegende Papier zeigt in den folgenden beiden Kapiteln den theoretischen Bezugsrahmen der Studie und die methodische Vorgehensweise. Daraufhin werden die Ergebnisse sowohl der quantitativen als auch der qualitativen Studie dargestellt und im Rahmen der Diskussion miteinander verbunden.
Keywords: Motivationsentwicklung; Hochschule; motivation; Längsschnitt; Mixed Methods

Self-Regulation and Entrepreneurial Learning - Fust, Alexander; Jenert, Tobias
Research on entrepreneurial learning often stresses the role of experience and previous knowledge. We aim to advance this perspective by pointing out the prerequisites and limitations of experience-based forms of learning and by adapting findings from educational psychology to the entrepreneurial context. Developing a model of self-regulated entrepreneurial learning (SREL) we pursue a more process oriented view of entrepreneurial learning in order to explain how learning unfolds in contexts of uncertainty and novelty when relevant experience and knowledge are scarce. The model comprises a planning, a performance and a review phase in order to support entrepreneurs in their learning process. It is suggested how SREL is related to self-efficacy, emotions and cognitive biases.
Keywords: Unternehmertum; lernen

The crucial first year: The development of students' motivation at a Business School-a Mixed Methods Study - Brahm, Taiga; Jenert, Tobias
The transition from school to university can be overwhelming for some students. While students' motivation is considered a strong predictor of performance, the development of motivation during students' transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present mixed methods study addresses this research gap and examines the development of economics students' study motivation. The longitudinal mixed-method study included three waves of data collected using quantitative surveys and a series of five interviews conducted with 14 first-year students over eight months. Regarding students' development over time, the quantitative analysis showed a gradual decline in students' motivation. However, in the interviews, certain events during the first year were identified as critical incidents demotivating students. These insights into the development of students' motivation at a business school show that concrete incidents influence students' motivational development; thus, they could be transformed by structural changes.
Keywords: motivation; business school; higher education; latent growth curve model; longitudinal study; mixed methods; interview; students

Transition within higher education institutions (HEI): Differences in learning culture (LC) between first-year, bachelor, and master students at a business school - Gebhardt, Anja; Jenert, Tobias
Tertiary education comprises at least two phases, undergraduate and graduate studies. Often, the first year is regarded another, crucial phase where students familiarize with the study environment. It can be hypothesized that students' individual perceptions of learning and studying as well as the pedagogies they experience differ depending on their current study phase. Yet, differences between the phases in HE have rarely been investigated. To capture differences in student experiences in HE comprehensively, Jenert and Gebhardt (2010) have developed a framework describing Learning Culture in HEI. LC comprises a number of constructs on the three levels of the individual student, pedagogical interactions and the organization. The study first aims to quantitatively describe differences in LC between the phases of HE within a university. Based on this analysis, a second goal is to develop a deeper understanding of how students manage the transitions between different phases by applying qualitative research methods.
Keywords: Higher Education; Transitions; Bachelor; Master

Wie kann über DBR die wissenschaftliche und praktische Relevanz der Forschung gesichert werden? - Brahm, Taiga; Jenert, Tobias
Auseinandersetzungen über Forschungsmethodologien haben in den Bildungswissenschaften lange Tradition. Sie werden häufig unversöhnlich und mit Profilierung der Gegensätze geführt. Für uns hängt die Sinnhaftigkeit einer Forschungskonzeption von der Problemstellung und dem Erkenntnisinteresse ab. Dies gilt auch für Design-Based Research (DBR). Dieser Ansatz entstand als Reaktion auf die Kritik an mangelnder praktischer Anwendung von Befunden aus der empirisch-analytischen Lehr-Lernforschung. Als Ergebnis werden Theorien angestrebt, die für die Praxis einen Nutzen bieten und zugleich über die Anwendung in einer singulären Situation hinausgehen. Wir wollen folgenden Fragen nachgehen: Wo liegen die Gemeinsamkeiten, wo die Spezifika von DBR gegenüber bestehenden Methodologien? Wie wird der Generalisierungsanspruch von Theorien innerhalb von DBR verstanden und umgesetzt? Für welche Erkenntnisinteressen eignet sich DBR? Welche Methoden sind für DBR sinnvoll und können wie angewendet werden?
Keywords: design-based research; gestatlungsbasierte Forschung; Erziehungswissenschaft; Design; Mixed Methods

Verändern Medien die Lernkultur? Mögliche Rollen von Technologie zwischen virtuellen und physischen Lernräumen - Jenert, Tobias (Lernumgebungen an der Hochschule. Auf dem Weg zum Campus von morgen)

Viel Neues und doch keine Innovation!?: Fünf Thesen, warum es die Lehrentwicklung an Hochschulen schwer ha - Jenert, Tobias

Change Management in Higher Education Institutions - Brahm, Taiga; Jenert, Tobias

Modelling long-range dependence and trends in duration series: an approach based on EFARIMA and ESEMIFAR models - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita (Statistical Papers)

On EFARIMA and ESEMIFAR Models - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita (Empirical Economic and Financial Research)

Double Conditional Smoothing of High-Frequency Volatility Surface Under a Spatial Model - Peitz, Christian; Feng, Yuanhua (Empirical Economic and Financial Research)

Data-driven estimation of diurnal patterns of durations between trades on financial markets - Feng, Yuanhua (Statistics & Probability Letters)

Data-driven estimation of realized kernels under dependent microstructure noise and further analysis using the Semi-FI-Log-ACD - Zhou, Chen; Feng, Yuanhua

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren